New opportunities for fracture healing detection: Impedance spectroscopy measurements correlate to tissue composition in fractures. Issue 12 (9th June 2017) - Lin, Monica C.; Yang, Frank; Herfat, Safa T.; Bahney, Chelsea S.; Marmor, Meir; Maharbiz, Michel M.
ABSTRACT: Accurate evaluation of fracture healing is important for clinical decisions on when to begin weight‐bearing and when early intervention is necessary in cases of fracture nonunion. While the stages of healing involving hematoma, cartilage, trabecular bone, and cortical bone have been well characterized histologically, physicians typically track fracture healing by using subjective physical examinations and radiographic techniques that are only able to detect mineralized stages of bone healing. This exposes the need for a quantitative, reliable technique to monitor fracture healing, and particularly to track healing progression during the early stages of repair. The goal of this study was to validate the use of impedance spectroscopy to monitor fracture healing and perform comprehensive evaluation comparing measurements with histological evidence. Here, we show that impedance spectroscopy not only can distinguish between cadaver tissues involved throughout fracture repair, but also correlates to fracture callus composition over the middle stages of healing in wild‐type C57BL/6 mice. Specifically, impedance magnitude has a positive relationship with % trabecular bone and a negative relationship with % cartilage, and the opposite relationships are found when comparing phase angle to these same volume fractions of tissues. With this information, we can quantitatively evaluate how far a fracture has progressed through the healing stages. Our results demonstrate the feasibility of impedance spectroscopy for detection of fracture callus composition and reveals its potential as a method for early detection of bone healing and fracture nonunion. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2620–2629, 2017.